Drivers of change in Ghana's cocoa sector - Vigneri, Marcella (International Food Policy Research Institute, 2008)
Using a two year panel dataset, this paper offers an empirical investigation of the unprecedented production boom episode observed in Ghana's cocoa sector between 2002 and 2004. We look at the technology of production underlying the years of the boom, and suggest that most of the rise was due to a more intensive use of household labor, good weather, and to some extent the increased use of fertilizer. The drivers of the recent production boom in Ghana did not, however, alter the more fundamental and long-standing problems of the sector. Cocoa yields in Ghana remain well behind those observed in other producing countries and the key constraint of the sector remains its lack of innovation. Current production technology in the cocoa sector is labor-using and land saving, whereas it is labor that is scarce to the household. This poses more serious concerns about the incentives and policies required to promote and sustain technological innovation in the sector.